Tissue‐Adaptive Materials with Independently Regulated Modulus and Transition Temperature. Issue 50 (11th November 2020) - Zhang, Daixuan; Dashtimoghadam, Erfan; Fahimipour, Farahnaz; Hu, Xiaobo; Li, Qiaoxi; Bersenev, Egor A.; Ivanov, Dimitri A.; Vatankhah‐Varnoosfaderani, Mohammad; Sheiko, Sergei S.
Abstract: The ability of living species to transition between rigid and flexible shapes represents one of their survival mechanisms, which has been adopted by various human technologies. Such transition is especially desired in medical devices as rigidity facilitates the implantation process, while flexibility and softness favor biocompatibility with surrounding tissue. Traditional thermoplastics cannot match soft tissue mechanics, while gels leach into the body and alter their properties over time. Here, a single‐component system with an unprecedented drop of Young's modulus by up to six orders of magnitude from the GPa to kPa level at a controlled temperature within 28–43 ° C is demonstrated. This approach is based on brush‐like polymer networks with crystallizable side chains, e.g., poly(valerolactone), affording independent control of melting temperature and Young's modulus by concurrently altering side chain length and crosslink density. Softening down to the tissue level at the physiological temperature allows the design of tissue‐adaptive implants that can be inserted as rigid devices followed by matching the surrounding tissue mechanics at body temperature. This transition also enables thermally triggered release of embedded drugs for anti‐inflammatory treatment. Abstract : Bottlebrush elastomers with crystallizable side chains undergo dramatic softening transition upon heating. At body temperature, ≈37 °C,  these materials drop their modulus by up to six orders of magnitude, transitioning from hard plastic to tissue‐like elastomer with transition temperature and modulus controlled by the brush architecture. Simultaneously, materials softening triggers drug release, thus highlighting their potential as tissue‐adaptive implants.